Several Methodical Essential Principles of Internal Medicine`s Teaching - P. P. Slavny (Медицинский вестник Юга России, 2011)
In the article it was discussed some essential components of program internal medicine`s teaching. Conducting patients with writing and defense of case history is a significant part of studies. Another important part of professional training for future physicians is analysis, discussion and sometimes independent modeling of clinical sums, which promotes development of analytical and synthetical function for thinking. One more significant section is still studying of electrocardiography, that because of information`s volume naturally impossible to get into one lession, that`s why expediently to give daily a small amount of time for this purpose. A primary aim of this article is an attracting young teacher to lesion`s dynamics, and also a changing activity, a rhythm of work, which promotes formation of a stable interest to education.